Health Talk Education On The Importance Of Peer Group Support For The Prolanis Community: A Community Service Program Approach - Sugiharto, Agus; Asti Werdhani, Retno; Kusumadewi, Dian; Sefiany Koloi, Vican; Rahmi, Siti (CV. Inara, 2025)
The Chronic Disease Management Program (Prolanis) is an initiative in the health care system that aims to improve the quality of life of people with chronic diseases, such as diabetes mellitus and hypertension. A key component of Prolanis's effectiveness is social support, particularly peer group support, which can enhance patients' adherence to treatment and promote healthy living. This Health educational activity seeks to increase Prolanis participants' comprehension of the value of peer support in the management of chronic illnesses. The method used in this community service is Health Talk Education, using 3 stages, namely, preparation, implementation, evaluation, and follow-up. To conduct evaluation and follow-up, questionnaires are used to gauge participants' knowledge growth both before and after the activity, as well as the development of peer support. According to the activity's findings, participants' attitudes and awareness of the advantages of taking part in peer group support increased, and five peer group support groups were formed, each with five members. In addition, active participation in the discussion indicated the high enthusiasm of participants to form and strengthen a support community in the Prolanis community environment. This community service initiative received excellent feedback from participants. Through a more comprehensive strategy founded on social support, it is anticipated that this community-based education will help Prolanis patients have a greater quality of life.